If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(n-1)=12
We simplify the equation to the form, which is simple to understand
3(n-1)=12
Reorder the terms in parentheses
+(+3n-3)=12
Remove unnecessary parentheses
+3n-3=+12
We move all terms containing n to the left and all other terms to the right.
+3n=+12+3
We simplify left and right side of the equation.
+3n=+15
We divide both sides of the equation by 3 to get n.
n=5
| .2b=16 | | x*2+46=5*x-11 | | -6x-8+8x=-7x+4 | | 75=x*2.51x | | 2(3x-5)=7x+1 | | 1x+8y=38.5 | | 5x+6-2x=-6+x | | x^2-9x-41=-3x-1 | | 8x+6+2(4x-7)= | | 13-2x=2x-3 | | -7x+9=-8x-3 | | 13x^2+6x-4=0 | | 200=x*2x | | 3t+4=t+-3 | | 3vx^2=24v | | -57x+62=17+22x | | 20x+10+30x-2+7x+1= | | 2m+1=17 | | 7+Y=18.2-Y | | 2x+2=57 | | 6+78x=39x+12 | | x^3-5x^2+7x+51=0 | | x^2+8x+19=7 | | 9y-13=35 | | 20x-32=238-8x | | 7=x/360*3.14*64 | | 2x-3=5x-11 | | y^2-14y+18=-4y-6 | | 4+Y+5=17-2 | | x^2=(x+1)(x+1) | | 6x+78x=39x+12 | | T^2-11t=7 |